2014
DOI: 10.1097/rlu.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radioactive Iodine Therapy on Lacrimal Gland Functions in Patients With Hyperthyroidism

Abstract: In our study, we concluded that the decrease in mucin and aqueous production occurs due to affected lacrimal glands by RAI therapy; however, this effect is not dose dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The mean RAI dose in the hyperthyroid group was 603.1 MBq (ranging from 481 to 740 MBq); in the cancer group, it was 3700 MBq (mean and total). A low-iodine diet was prescribed 10 days before the therapy, and antithyroid medications were withdrawn 7 days before the therapy began 2,5 . RAI treatment was administered orally to all patients.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean RAI dose in the hyperthyroid group was 603.1 MBq (ranging from 481 to 740 MBq); in the cancer group, it was 3700 MBq (mean and total). A low-iodine diet was prescribed 10 days before the therapy, and antithyroid medications were withdrawn 7 days before the therapy began 2,5 . RAI treatment was administered orally to all patients.…”
Section: Methodsmentioning
confidence: 99%
“…2 Although it is a safe treatment, 131 I may accumulate in extrathyroidal tissues such as gastric mucosa, intestine, choroid plexus, salivary glands, sweat glands, and lacrimal glands. [3][4][5] In particular, the literature has reported that the salivary gland is damaged and leads to dry mouth. [6][7][8] Since the lacrimal gland is a tissue with similar properties to the salivary gland, it has been investigated with the assumption that iodine may also affect tear secretion.…”
mentioning
confidence: 99%
See 3 more Smart Citations